Thermal runaway of 314 Ah LiFePO4 battery induced by overcharging with different rate and thermal runaway suppression based on liquid thermal management - Jialong Liu; E Chun; Wei Liu; Xiaoming Jin; Hui Zhang; Jialei Liu; Zhirong Wang (Process Safety and Environmental Protection, 2026)

Quality changes in the physiology, behaviour, nutrition, and taste of Urechis unicinctus during waterless live transportation - Teng Teng; Yuchun Lu; Zichen Deng; Shuqi Wang; Yuting Yang; Huihong Li; Chun-E Liu (Food Chemistry, 2025)

The effect of heatwave and cold spell on cardiovascular disease mortality in central China, 2018–2022 - Ling-Shuang Lv; Li Yin; Yuan Liu; Chun-Liang Zhou; Ji Hu; Ning An; Xian Xie; Xing-E Zhang; Min Zhang; Xiu-Ying Liu (International Journal of Biometeorology, 2025)

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

In-vitro method and model to estimate methane emissions from liquid manure management on pig and dairy farms in four countries - Søren O. Petersen; Chun Ma; Julio E. Hilgert; Kristina Mjöfors; Paria Sefeedpari; Barbara Amon; André Aarnink; Balázs Francó; Federico Dragoni; Karin Groenestein; Steen Gyldenkærne; Christiane Herrmann; et al. (Journal of Environmental Management, 2024)

Bacterial, short-chain fatty acid and gas profiles of partially hydrolyzed guar gum in vitro fermentation by human fecal microbiota - Xiong-E Pi; Hao Fu; Xiao-Xia Yang; Zai-Chun Yu; Wei-Lin Teng; Yinjun Zhang; Xue-Wei Ye; Hui Hui Quan; Li-Zhi Lu; Wei Liu (Food Chemistry, 2024)

Hirsutinolide-type sesquiterpenoids with anti-prostate cancer activity from Cyanthillium cinereum - Song Ang; Chun Liu; Peng Hong; Lei Yang; Gui'e Hu; Xi Zheng; Jingwei Jin; Rihui Wu; Wing-Leung Wong; Kun Zhang; Lishe Gan; Dongli Li (Phytochemistry, 2023)

Assessing the joint effects of brain aging and gut microbiota on the risks of psychiatric disorders - Huijie Zhang; Li Liu; Shiqiang Cheng; Yumeng Jia; Yan Wen; Xuena Yang; Peilin Meng; Chun’e Li; Chuyu Pan; Yujing Chen; Zhen Zhang; Jingxi Zhang; et al. (Brain Imaging and Behavior, 2022)

Impact of ambient temperature on life loss per death from cardiovascular diseases: a multicenter study in central China - Ling-Shuang Lv; Chun-Liang Zhou; Dong-Hui Jin; Wen-Jun Ma; Tao Liu; Yi-Jun Xie; Yi-Qing Xu; Xing-E Zhang (Environmental Science and Pollution Research, 2022)
Background In the context of global climate change, studies have focused on the ambient temperature and mortality of cardiovascular diseases (CVDs). However, little is known about the effect of ambient temperature on year of life lost (YLL), especially the life loss per death caused by ambient temperature. In this study, we aimed to assess the relationship between ambient temperature and life loss and estimate the impact of ambient temperature on life loss per death. Methods We collected daily time series of mortality and meteorological data from 70 locations in Hunan province, central China, in periods ranging from Jan. 1, 2013, to Dec. 31, 2017. Crude rates of YLL were calculated per 100,000 people per year (YLL/100,000 population) for each location. A distributed lag nonlinear model and multivariate meta-regression were used to estimate the associations between ambient temperature and YLL rates. Then, the average life loss per death attributable to ambient temperature was calculated. Results There were 711,484 CVD deaths recorded within the study period. The exposure-response curve between ambient temperature and YLL rates was inverted J or U-shaped. Relative to the minimum YLL rate temperature, the life loss risk of extreme cold temperature lasted for 10 to 12 days, whereas the risk of extreme hot temperature appeared immediately and lasted for 3 days. On average, the life loss per death attributable to non-optimum ambient temperatures was 1.89 (95% CI, 1.21-2.56) years. Life loss was mainly caused by cold temperature (1.13, 95% CI, 0.89‑1.37), particularly moderate cold (1.00, 95% CI, 0.78‑1.23). For demographic characteristics, the mean life loss per death was relatively higher for males (2.07, 95% CI, 1.44‑2.68) and younger populations (3.72, 95% CI, 2.06‑5.46) than for females (1.88, 95% CI, 1.21-2.57) and elderly people (1.69, 95% CI, 1.28-2.10), respectively. Conclusions We found that both cold and hot temperatures significantly aggravated premature death from CVDs. Our results indicated that the whole range of effects of ambient temperature on CVDs should be given attention.

One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

The effect of substrate grain size on burrowing ability and distribution characteristics of Perinereis aibuhitensis - Tao Sun; Chun’e Liu; Xingzuo Li; Dongzhengyang An; Hairui Yu; Zheng Ma; Feng Liu (Acta Oceanologica Sinica, 2019)

Avian prenatal auditory stimulation: progress and perspectives - Moises Rivera; Matthew I. M. Louder; Sonia Kleindorfer; Wan-chun Liu; Mark E. Hauber (Behavioral Ecology and Sociobiology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Functional genes and thermophilic microorganisms responsible for arsenite oxidation from the shallow sediment of an untraversed hot spring outlet - Ye Yang; Yao Mu; Xian-Chun Zeng; Weiwei Wu; Jie Yuan; Yichen Liu; E. Guoji; Feng Luo; Xiaoming Chen; Hao Li; Jianing Wang (Ecotoxicology, 2017)

Nonlinear fault detection threshold optimization method for RAIM algorithm using a heuristic approach - Pan He; Gang Liu; Chun Tan; Yan-e Lu (GPS Solutions, 2016)

Ecological suitability assessment and introduction experiment on Rosa damascena trigintipetala in Sichuan Province, China - Xiao-lan Wang; Chun-jiang Su; Li Peng; Hai-e Wang; Hai-ming Wang; Wei Liu; Ping Li; Yan Fang (Journal of Mountain Science, 2014)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Effects of Edaravone on Amyloid-β Precursor Protein Processing in SY5Y-APP695 Cells - Yue-E Shen; Yan Wang; Gui-Chun Yu; Chao Liu; Zhen-Yu Zhang; Li-Ming Zhang (Neurotoxicity Research, 2013)

Ion Composition of Fog Water and Its Relation to Air Pollutants during Winter Fog Events in Nanjing, China - Jun Yang; Yu-Jing Xie; Chun-E Shi; Duan-Yang Liu; Sheng-Jie Niu; Zi-Hua Li (Pure and Applied Geophysics, 2012)

Chronic cocaine exposure induces putamen glutamate and glutamine metabolite abnormalities in squirrel monkeys - Xiaoxu Liu; J. Eric Jensen; Timothy E. Gillis; Chun S. Zuo; Andrew P. Prescot; Melanie Brimson; Kenroy Cayetano; Perry F. Renshaw; Marc J. Kaufman (Psychopharmacology, 2011)

Total nitrogen deposition at key growing stages of maize and wheat as affected by pot surface area and crop variety - Chun-E He; Xin Wang; Xuejun Liu; Andreas Fangmeier; Peter Christie; Fusuo Zhang (Plant and Soil, 2011)

Globular adiponectin regulates energy homeostasis through AMP-activated protein kinase–acetyl-CoA carboxylase (AMPK/ACC) pathway in the hypothalamus - Jun-Ping Wen; Chun-e Liu; Ya-Ting Hu; Gang Chen; Li-xiang Lin (Molecular and Cellular Biochemistry, 2010)

Large-Eddy Simulation of Flow and Pollutant Transport in Urban Street Canyons with Ground Heating - Xian-Xiang Li; Rex E. Britter; Tieh Yong Koh; Leslie K. Norford; Chun-Ho Liu; Dara Entekhabi; Dennis Y. C. Leung (Boundary-Layer Meteorology, 2010)

Genomics of hybrid poplar ( Populus trichocarpa × deltoides ) interacting with forest tent caterpillars ( Malacosoma disstria ): normalized and full‐length cDNA libraries, expressed sequence tags, and a cDNA microarray for the study of insect‐induced defences in poplar - STEVEN RALPH; CLAIRE ODDY; DAWN COOPER; HESTHER YUEH; SHARON JANCSIK; NATALIA KOLOSOVA; RYAN N. PHILIPPE; DANA AESCHLIMAN; RICK WHITE; DEZENE HUBER; CAROL E. RITLAND; FRANÇOIS BENOIT; et al. (Molecular Ecology, 2006)
As part of a genomics strategy to characterize inducible defences against insect herbivory in poplar, we developed a comprehensive suite of functional genomics resources including cDNA libraries, expressed sequence tags (ESTs) and a cDNA microarray platform. These resources are designed to complement the existing poplar genome sequence and poplar ( Populus spp.) ESTs by focusing on herbivore‐ and elicitor‐treated tissues and incorporating normalization methods to capture rare transcripts. From a set of 15 standard, normalized or full‐length cDNA libraries, we generated 139 007 3′‐ or 5′‐end sequenced ESTs, representing more than one‐third of the c. 385 000 publicly available Populus ESTs. Clustering and assembly of 107 519 3′‐end ESTs resulted in 14 451 contigs and 20 560 singletons, altogether representing 35 011 putative unique transcripts, or potentially more than three‐quarters of the predicted c. 45 000 genes in the poplar genome. Using this EST resource, we developed a cDNA microarray containing 15 496 unique genes, which was utilized to monitor gene expression in poplar leaves in response to herbivory by forest tent caterpillars ( Malacosoma disstria ). After 24 h of feeding, 1191 genes were classified as up‐regulated, compared to only 537 down‐regulated. Functional classification of this induced gene set revealed genes with roles in plant defence (e.g. endochitinases, Kunitz protease inhibitors), octadecanoid and ethylene signalling (e.g. lipoxygenase, allene oxide synthase, 1‐aminocyclopropane‐1‐carboxylate oxidase), transport (e.g. ABC proteins, calreticulin), secondary metabolism [e.g. polyphenol oxidase, isoflavone reductase, (–)‐germacrene D synthase] and transcriptional regulation [e.g. leucine‐rich repeat transmembrane kinase, several transcription factor classes (zinc finger C3H type, AP2/EREBP, WRKY, bHLH)]. This study provides the first genome‐scale approach to characterize insect‐induced defences in a woody perennial providing a solid platform for functional investigation of plant–insect interactions in poplar.

Noninvasive Assessment of Tumor Hypoxia with 99mTc Labeled Metronidazole - David J. Yang; Seyfettin Ilgan; Tetsuya Higuchi; Fereshteh Zareneyrizi; Chang-Sok Oh; Chun-Wei Liu; E. Edmund Kim; Donald A. Podoloff (Pharmaceutical Research, 1999)